Joyce writing disability - Colangelo, Jeremy, 1990-; Linett, Maren Tova (Florida James Joyce series., 2022)
"In this book, the first to explore the role of disability in the writings of James Joyce, contributors examine the varying ways in which Joyce's texts represent disability and the environmental conditions of his time that stigmatized, isolated, and othered individuals with disabilities"--